2022
DOI: 10.1371/journal.pone.0270231
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of probiotic, chicory root powder and coriander seed powder on growth performance, antioxidant activity and gut health of broiler chickens

Abstract: Gut health plays an important role on production and performance of broilers. This trial was undertaken with an aim to evaluate the synergistic effect of probiotic, chicory root powder and coriander seed powder on the performance and gut health of broiler chicken. For this purpose, a total of 240 day-old broiler chicks were randomly allotted to six dietary treatments with 8 replicates of 5 birds in each. Treatment groups included T1 as control i.e., basal diet (BD) without any growth promoter and T2—BD + antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…However, inulin derived from dahlia tuber extract and Lactobacillus acidophilus are important for improving antioxidant enzyme functions in mediating the better balance of intestinal microflora found in the current study (Table 3). The present results were in accordance with the most recent report (Gurram et al, 2022) that the increased GSH-Px and SOD were associated with the improvement of bacterial balance (higher LAB, lower E. coli and Salmonella counts) due to March 2023 101 the feeding effect of probiotic and inulin from chicory root. This physiological condition could be considered to have a potential effect on poultry production on one side.…”
Section: Protein and Amino Acids Digestibilitysupporting
confidence: 94%
“…However, inulin derived from dahlia tuber extract and Lactobacillus acidophilus are important for improving antioxidant enzyme functions in mediating the better balance of intestinal microflora found in the current study (Table 3). The present results were in accordance with the most recent report (Gurram et al, 2022) that the increased GSH-Px and SOD were associated with the improvement of bacterial balance (higher LAB, lower E. coli and Salmonella counts) due to March 2023 101 the feeding effect of probiotic and inulin from chicory root. This physiological condition could be considered to have a potential effect on poultry production on one side.…”
Section: Protein and Amino Acids Digestibilitysupporting
confidence: 94%
“…Kollanoor Johny et al described the ability of trans-cinnamaldehyde to effectively reduce Salmonella in the caecum [ 52 ]. Gurram et al showed a significant reduction in Salmonella in the ileum when fed a mixture of probiotics, chicory, and coriander [ 53 ]. Zou et al found a significant reduction in Salmonella in the ileum when broiler chickens were fed a mixture of turmeric, hops, and grape seed extract [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al showed that fenugreek extract fed to broiler chickens from the third day of life improved daily weight gain [ 57 ]. Gurram et al fed feed supplements containing probiotics, chicory, and coriander, or combinations of these, and found significantly better weight gain in all treatment groups compared to the control group [ 53 ]. Zou et al fed a mixture of turmeric, hops, and grape seed extract to broiler chickens at certain life stages and found significantly better weight gain compared to controls [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a probiotic with chicory or coriander seed powder reduced the content of E. coli and Salmonella spp. in the small intestine of chickens ( Gurram et al, 2022 ). Higher antibody titers against ND were found using a probiotic with garlic ( Elbaz et al, 2021 ).…”
Section: Pathways Of Immunostimulation and Immunomodulationmentioning
confidence: 99%